A prática pedagógica e a construção do conhecimento científico (Práxis Educativa, 2009)
The present work intends to present relative facts to the evolution of the scientific knowledge, and the first rupture in terms of conception of the knowledge felt starting from the jump of the mythical vision for the reason. It also intends to list the influences of the dominant paradigm of the science in the areas of the knowledge. It discusses in a resumed form the emergent paradigm, detaching some necessary beginnings so that the educational practice propitiates the construction of the knowledge.Keywords: Dominant paradigm. Emergent paradigm. Pedagogic practice. Reproduction/construction of the knowledge.